Urgensi Akad Dalam Transaksi Keuangan Syariah - Syarofi, Muhammad; Mu’awanah, Mu’awanah; Sa’diya, Nadia Silviatus (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2023)
This note will examine how the presence of contracts has a critical role in sharia financial business with the many interrelationships that arise. One of them is that in Islam there is independence to carry out a contract by determining the terms and form of the contract desired by the parties, provided that the contract is carried out sincerely and is not subject to the prohibitions of the Shari'a. Based on that, the essence of contracts carried out in Islam is to create benefits for the parties who enter into an agreement for a sharia financial business. In principle, sharia contracts should have Islamic legal principles which include the principle of independence, the principle of meeting, the principle of equality. Fourth, the basis of sincerity or consensualism, the basis of honesty and evidence, the basis of usefulness, and the basis for recording agreements that are entered into must be stated in records that can be legally accounted for.